Synthesis Of Nickel (Ni) Doped HKUST-1 using Solvotermal Method with Addition of Acetic Acid as Modulator - Farhan Fikri Safii; Ratna Ediati (IPTEK Journal of Proceedings Series, 2015)
Hong Kong University of Science and Technology-1 (HKUST-1) is metal organic framework (MOF) that composed from ligand BTC (1,3,5-benzene tricarboxylic) and copper ions. The method used in this study is solvotermal with variations nickel ion doping and additions acetic acid as modulator. The purpose of this study is to increase the hydrogen storage capacity. The results obtained were characterized by XRD showed that the HKUST-1 and Ni-HKUST-1 has formed, showed by peaks at 2 theta = 6.7, 9.5, 11.6, 13.4, and 19.0.